A Educação Matemática Muda - Fernandes, Filipe Santos [UNESP] (FapUNIFESP (SciELO), 2016)
Once a famous linguistic was challenged to grammarize a book of endless pages. Led by the word change, the man talk about Mathematics Education drawing three senses: the one of the noun, the one of the verb and the one of the adjective. Unfinished drawings, drafts of a notebook built in a hopeless manner. Between narratives and productions of meaning, thinking of affection of a social practice, the Mathematics Education.
Mathematics education changes
Keywords: Mathematics Education; Narrative; Social Practice